Pathomechanisms of a CLCN1 Mutation Found in a Russian Family Suffering From Becker's Myotonia - Altamura, Concetta; Ivanova, Evgeniya A.; Imbrici, Paola; Conte, Elena; Camerino, Giulia Maria; Dadali, Elena L.; Polyakov, Alexander V.; Kurbatov, Sergei Aleksandrovich; Girolamo, Francesco; Carratù, Maria Rosaria; Desaphy, Jean-François (Frontiers in Neurology, 2020)
Objective. Myotonia congenita (MC) is a rare muscle disease characterized by sarcolemma over-excitability inducing skeletal muscle stiffness. It can be inherited either as an autosomal dominant (Thomsen's disease) or an autosomal recessive (Becker's disease) trait. Both types are caused by loss-of-function mutations in the CLCN1 gene, encoding for ClC-1 chloride channel. We found a ClC-1 mutation, p.G411C, identified in Russian patients who suffered from a severe form of Becker's disease. The purpose of this study was to provide a solid correlation between G411C dysfunction and clinical symptoms in the affected patient. Methods. We provide clinical and genetic information of the proband kindred. Functional studies include patch-clamp electrophysiology, biotinylation assay, western blot analysis, and confocal imaging of G411C and wild-type ClC-1 channels expressed in HEK293T cells. Results. The G411C mutation dramatically abolished chloride currents in transfected HEK cells. Biochemical experiments revealed that the majority of G411C mutant channels did not reach the plasma membrane but remained trapped in the cytoplasm. Treatment with the proteasome inhibitor MG132 reduced the degradation rate of G411C mutant channels, leading to their expression at the plasma membrane. However, despite an increase in cell surface expression, no significant chloride current was recorded in the G411C-transfected cell treated with MG132, suggesting that this mutation produces nonfunctional ClC-1 chloride channels. Conclusion. These results suggest that the molecular pathophysiology of G411C is linked to a reduced plasma membrane expression and biophysical dysfunction of mutant channels, likely due to a misfolding defect. Chloride current abolition confirms that the mutation is responsible for the clinical phenotype.